Spectroscopic studies of oligomers containing 2,5-trans furanoid sugar amino acids. - Edwards, A; Alexander, B; Fleet, G; Tranter, G (2008)
Sugar amino acids and their oligomers, known as carbopeptoids, are commonly studied as foldamers. However, study of their conformational preference is often challenging when the adopted conformations are extended and/or disordered. This study is the first to explore the disordered nature of such carbopeptoids by utilizing a family of 2,5-trans carbopeptoids. An array of spectroscopic techniques has been used to investigate the conformational preference of these carbopeptoids. However, using this data alone it has not been possible to assign conformational preference as an ordered extended conformation or as a disordered family of closely related conformations. Computational methods need to be employed to achieve reliable interpretation of the spectroscopic data.